Caries Risk Profiles amongst Preschool Aged Children Living in the Sleman District of Yogyakarta, Indonesia - Widita, Elastria; Pamardiningsih, Yuni; Vega, Christia AW. (UI Scholars Hub, 2017)
Objective: To assess the caries risk factors of preschool aged children. Methods: Data was collected from a sample of 85 preschool children and their mothers. An interview, and a clinical and microbiology assessment was included in this study. Clinical examinations were performed to measure the dental caries experience and plaque visibility of the children and mothers. The presence and levels of Mutans Streptococci (MS) in the saliva was measured using a commercial kit by Dentocult SM and evaluated using the manufacturer’s chart. Results: Sixty-five children had a high risk of caries (76.5%), 12.9% had a low risk, and 10.6% had a moderate risk of caries. Active cavities were found in more than half of the mothers and children. The majority of the child subjects had a snacking habit between meals (85.9%). High risk scores of 2 and 3, indicating salivary levels of MS, was found in 41.1% of children. Fluoride exposure experienced by the study population was very limited. Conclusion: Results suggest that the majority of the population had a high caries risk. There was a high occurrence of teeth with cavities in children and active carious lesions in the mothers. There was a high frequency in snacking habits, the presence of plaque and bleeding gums, high levels of salivary MS, and low protective factors for the children. Results suggest that management of caries related factors are needed in order to prevent caries in the future.